2007
DOI: 10.1111/j.1532-5415.2007.01571.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Endurance in Elderly Nursing Home Residents Is Related to Fatigue Perception, Mobility, and Circulating Tumor Necrosis Factor‐Alpha, Interleukin‐6, and Heat Shock Protein 70

Abstract: Elderly nursing home residents complaining of fatigue need to be taken seriously, because they show worse muscle endurance, which is related to poorer mobility. Inflammatory processes involving TNF-alpha and the interaction between IL-6 and Hsp70 are related to poorer muscle endurance in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 35 publications
3
47
0
Order By: Relevance
“…The comparison of our results with the two studies of Bautmans et al 21,31 was not possible due to the methodological differences. In this study we assessed the knee extensors using an isokinetic protocol of dynamic muscle contractions, while in the studies of Bautmans, a hand dynamometer and a protocol of isometric contraction of wrist's muscles were used 21,31 . The samples of the studies of Bautmans et al 21,31 were varied; in one study, it was composed of community-dwelling older adults without inflammation 21 and, in the other, by institutionalized elderly affected by evident inflammatory process 31 .…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…The comparison of our results with the two studies of Bautmans et al 21,31 was not possible due to the methodological differences. In this study we assessed the knee extensors using an isokinetic protocol of dynamic muscle contractions, while in the studies of Bautmans, a hand dynamometer and a protocol of isometric contraction of wrist's muscles were used 21,31 . The samples of the studies of Bautmans et al 21,31 were varied; in one study, it was composed of community-dwelling older adults without inflammation 21 and, in the other, by institutionalized elderly affected by evident inflammatory process 31 .…”
Section: Discussionmentioning
confidence: 66%
“…The findings of the literature on the subject are conflicting; Bautmans et al 21 studying a sample of older adults, found negative and significant correlation of self-perceived fatigue with the manual muscle fatigue 21 . However, the same group of researchers, in another study in 2008, investigating a sample of elderly subjects, found no correlation between self-perceived fatigue and manual muscle fatigue 31 . The comparison of our results with the two studies of Bautmans et al 21,31 was not possible due to the methodological differences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations